Estudo da metilação de DNA de genes drivers na progressão do carcinoma medular da tiroide - Cardoso, Mirian Goncalves [UNIFESP] (2017)
Medullary thyroid carcinoma (CMT) originates from parafollicular or C-cells and comprises 5% of thyroid tumors. Mutations with gain of function on the RET oncogene are common in CMT, followed by those in the KRAS and HRAS genes. Recently, a large-scale genomic sequencing study did not identify additional mutations in CMT. This data together with the clinical observation that individuais with the same familial CMT mutation (CMTF) present different clinical evolutions led us to the following question: what epigenetic changes would contribute to the progression of CMT? Thus, the objective of this study was to verify if the aberrant DNA methylation could be a mechanism of inactivation of tumor suppressor genes as driver genes. In a first step, we studied genes pointed by the literature as potentially involved with the tumorigenesis of CMT. Among these studies, aberrant signaling of the NOTCH pathway was indicated resulting in a decrease in HES1 expression and increase of the tumor markers cromogranin and calcitonin in CMT. We verified whether the hypermethylation of HES1 could be responsible for the variable progression of CMT. We observed a variation of the meth.ylation and expression of HES1 in vitro suggesting relationship with the type of mutation in RET. In a second step, we sought to expand the search for new driver genes in CMT using a global genomic genomic analysis platform (Infinium 27K Methylation array). Among these genes, we identified and chose to study the chromodomain helicase DNA binding protein 5 (CHD5) tumor suppressor gene because it was associated with the development of neuroblastoma. We also observed that CHD5 is hypermethylated in the CMT cell line (TT cells, with the RET p.C634R genotype) and in paraffin embedded tumor samples. Treatment of the TT line with 5-aza-deoxycytidine (DAC) restored CHD5 expression, suggesting a regulation mediated by DNA methylation. We also assessed whether there was a possible epigenetic signature associated with CMT progression; For that, we also studied 17 tumor samples with the same mutation in RET (p.M918T) with different stages of tumor progression and survival time, for which we used a new platform of expanded CpG (850K beadchip DNA methylation array) . We did not find differentially methy/ated genes predictors of survival in a global analysis. However, through a particularized ana/ysis of genes, we found that the RASL 11B and UNC13A genes correlated with longer surviva/ time in patients with CMT exhibiting the RET p.M918T mutation. Identification of the differential methylation pattern of driver genes, both of the oncogene class and of tumor suppressors, may improve understanding of CMT biology and provide new therapeutic approaches and clinical prognostic indicators.